Shoulder Intra-Articular Temperature Is Higher In Patients With Small Rotator Cuff Tears Compared With Patients Who Have Larger Tears - Stefano Gumina, M.D., Ph.D; Marco Rionero, M.D; Jacopo Preziosi Standoli, P.T; Matteo Cantore, M.D; Vittorio Candela, M.D (Elsevier, 2023)
Purpose: To determine whether the intra-articular temperature of the shoulder correlates with the size of the tendon tear in patients with rotator cuff tears (RCTs). Methods: The shoulder intra-articular temperature of 75 consecutive (32 female, 43 male; mean age 61.12; standard deviation = 7.10) patients who underwent arthroscopic rotator cuff repair was measured with a digital thermometer, at first in 2 points (biceps anchor and glenoid labrum) during dry arthroscopy, followed by a third measurement during wet arthroscopy. A fourth measurement, represented by the patient's axillary body temperature, was taken upon admission. The RCTs were classified during surgery according to the Southern California Orthopedic Institute classification system as small, large, and massive. Data were submitted for statistical analysis. Results: The intra-articular temperature differs in patients with different-sized RCTs regardless of the location of the thermometer. A significantly higher temperature was found in patients with small RCTs (36.2°C ± 0.57°C) (P < .01). When the in-flow of the arthroscopic fluid was opened, the temperature dropped to an average of 24.5°C. Conclusions: The shoulder intra-articular temperature was significantly associated with RCT size. A significantly higher temperature was found in small RCTs. No correlation was found between age and sex, age and RCT size, sex and RCT size, or sex and temperature. Clinical Relevance: An early diagnosis and treatment of RCTs may avoid further degeneration and damage of the tendon caused by the increased temperature.